Analisis Nilai Tambah Melinjo pada Sentra Industri Emping di Desa Bandar Kecamatan Sukomoro Kabupaten Magetan - Adityaningrum, Eka; Marwanti, Sri; Rahayu, Wiwit (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2019)
Agricultural commodities are generally produced as raw materials and are easily damaged, so they need to be directly consumed or processed first. The processing can increase the added value of agricultural products. The purpose of this study was to determine the cost, revenue, profit, efficiency, and value added of melinjo chips industry in Industrial Center at  Bandar Village Sukomoro District Magetan Regency. The basic method of research used is descriptive analytical method. The determination of the sample area is purpossive which is Bandar Village Sukomoro District Magetan Regency because those village is the center of the melinjo chips industry in Magetan Regency. The respondents are found and gathered by using the proportional method and the respondents are found gathered simple random sampling method. The result of this research shows that total average cost spent by those industrialists in Bandar village is Rp5.816.109,00 per month. The average revenue for each of them is Rp7.826.667,00  per month and the profit is Rp2.010.492,00 per month. The running of melinjo chips industries is efficient. It can be known by efficiency value (R/C ratio) 1,42. The business of melinjo chips in Bandar Village, Sukomoro District, Magetan Regency provides added value of Rp. 8,645.00 / kg